Implementasi Manajemen dan Digitalisasi Perpustakaan di Lembaga Pendidikan Sekolah Dasar Negeri Lidah Kulon 1 Surabaya - Andini, Intan Tri; Billah, Zerlinda Talitha; Aini, Herlina Qurrota; Hasya, Siti Zakkiyah; Kusuma, Anggun Indah Nur; Fitria, Rezki Nurma; Sulistiyo, Adam; Akbar, Wildhan Falahati (TSAQOFAH, 2025)
This study examines the implementation of library management and digitalization at SDN Lidah Kulon 1 Surabaya as a response to the low reading interest among elementary school students. The primary objective is to analyze how structured library management and the use of digital platforms can improve student literacy. A qualitative descriptive method was employed, with data collected through interviews, observations, and documentation. The findings reveal that the library has a clear organizational structure involving the principal, head librarian, administrative staff, and technical services. The book classification system uses the Dewey Decimal Classification adapted with color schemes to facilitate access for young learners. The library is currently transitioning toward digitalization by utilizing the English Light and Inlislite applications, along with digital reading lists via Google Sheets. Literacy programs such as SAS (Sekolah AREK Surabaya) support literacy development through storytelling and writing activities. A partnership with Universitas Negeri Surabaya since 2022 has further strengthened the development of digital collections and provided digital literacy training for educational staff. However, the digitalization process still faces challenges such as limited internet access, low technological literacy among users, and copyright issues related to digital content. The study concludes that efficient library management and digital innovation contribute positively to improving student literacy, though the sustainability of such programs requires adequate infrastructure and ongoing training for library personnel.